High-capacity amorphous carbon-based negative electrode material and preparation method and application thereof

By introducing a large number of oxygen-containing functional groups into the amorphous carbon-based anode material and performing high-temperature carbonization treatment, the problems of low efficiency, low specific capacity and poor rate performance in the prior art are solved, and a high-capacity and high-efficiency sodium ion battery anode material is realized.

CN119612481APending Publication Date: 2025-03-14FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693654.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing amorphous carbon-based anode materials have low efficiency, low specific capacity and poor rate performance in sodium ion batteries for the first time, and are prone to excessive graphitization during the carbonization process, affecting the storage of Na ions.

Method used

By breaking and sieving the precursor carbon source, a large amount of oxygen-containing functional groups are introduced under the action of a strong oxidizing agent, and carbonizing is carried out at high temperatures to form a deep oxidized amorphous carbon anode material.

Benefits of technology

The reversible specific capacity and first-time Coulomb efficiency of amorphous carbon anode material were significantly improved. The first-time Coulomb efficiency reached ~90%, and the specific capacity was increased to >380mAh g-1, improving the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612481A_ABST
    Figure CN119612481A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a high-capacity amorphous carbon-based negative electrode material and a preparation method and application thereof.The preparation method comprises the steps that a large number of oxygen-containing functional groups are introduced into a crushed carbon source precursor through deep oxidation, the carbon layer spacing is enlarged, and then the disordered blocky amorphous carbon negative electrode material is obtained through high-temperature carbonization; heteroatoms introduced by the strong oxidant are converted into CH4, CO2 and other gases to leave the surface of the carbon source, so that the surface defects of the carbon source are reduced, the first coulombic efficiency is high, and the method is simple in process and can be applied to large-scale industrial production; a strong oxidant is selected to deeply oxidize a precursor, inert groups on the edge of a polygonal carbon ring can be oxidized into oxygen-containing active groups while a large number of oxygen-containing functional groups are introduced, the defects that common amorphous carbon is low in initial coulombic efficiency, low in specific capacity and poor in rate capability are further overcome, and the requirements of a lithium / sodium ion battery for a negative electrode material are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a high-capacity amorphous carbon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the price fluctuations and limited reserves of lithium resources have exerted great pressure on the future application of lithium-ion batteries (LIBs) in energy storage systems, especially in large-scale scenarios. Sodium-ion batteries (SIBs) are considered as potential alternatives to LIBs due to their abundant sodium resources, safety, and similar working principles to LIBs.

[0003] At present, the negative electrode material of sodium ion batteries is mainly amorphous carbon, which has abundant micropores and large carbon interlayer spacing, excellent storage capacity and low operating voltage, making it stand out among SIB negative electrode materials. However, the precursor carbon source is directly carbonized at high temperature (>1300℃), which easily forms carbon sheets with small interlayer spacing (d 002 ≤0.37nm), the first coulombic efficiency is low, between 70% and 80%. The capacity of amorphous carbon is mainly provided by the low-pressure platform with slow ion diffusion. Its short-range structure is orderly and the conductivity is insufficient, resulting in large voltage hysteresis at high rates and poor rate performance. Excessive graphitization is not conducive to the storage of Na ions. The Na storage capacity is ~280mAh g -1 , therefore, suppressing excessive graphitization during the carbonization process becomes a key factor in improving the Na storage capacity of amorphous carbon in SIBs.

[0004] When the focus is shifted back to the application of amorphous carbon anodes in lithium-ion storage, the defects, heteroatoms and functional groups of amorphous carbon itself provide a large number of lithium storage sites, which will lead to significant irreversible capacity loss in the initial cycle, resulting in low first coulombic efficiency (ICE). Therefore, improving the ICE while increasing the capacity of the lithiation platform is crucial for the application of amorphous carbon in the field of LIB. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a high-capacity amorphous carbon-based negative electrode material and a preparation method and application thereof, introduce a large number of oxygen-containing functional groups into the carbon-based material, expand the carbon layer spacing, and thereby improve the reversible specific capacity and ICE of the amorphous carbon negative electrode material for lithium / sodium ion batteries.

[0006] The technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a method for preparing a high-capacity amorphous carbon-based negative electrode material, comprising the following steps:

[0008] ① Crush the precursor carbon source and sieve it to d50 The value is between 3 and 20 μm;

[0009] ② subjecting the obtained precursor to an oxidation reaction with a strong oxidant at a reaction temperature of 40 to 120° C. and a reaction time of 30 to 240 min;

[0010] ③ Wash the precursor obtained in step ② with deionized water and filter until it is neutral;

[0011] ④ Treat the precursor treated in step ③ with high temperature carbonization for 1 to 6 hours under inert gas, and the temperature of high temperature carbonization is set to 1000 to 1700°C.

[0012] Preferably, the precursor carbon source includes one or more of asphalt, coconut shell charcoal, petroleum coke, coal, palm, bamboo powder, cellulose, wood powder, lignin, corn straw, starch, and phenolic resin.

[0013] Preferably, the strong oxidant includes one or more of iodic acid HIO3, concentrated sulfuric acid H2SO4, perchloric acid HClO4, concentrated hydrochloric acid HCI, concentrated nitric acid HNO3, and manganese dioxide MnO2.

[0014] Preferably, the molar concentration of the strong oxidant is 5-20 mol L -1 .

[0015] Preferably, the reaction speed of step ② is 200-800 r / min.

[0016] Preferably, the heating rate of the high temperature carbonization in step ④ is set to 1-10°C min -1 , gas flow rate is 10~40ml min -1 .

[0017] Preferably, the inert gas is Ar or N2.

[0018] Preferably, the precursor obtained by crushing and sieving in step ① is carbonized under inert gas for 1 to 12 hours before step ②, and the carbonization temperature is set to 200 to 800°C. The heating rate is set to 1 to 10°C min -1 , gas flow rate is 10~40mlmin -1 , the inert gas is Ar or N2.

[0019] The second aspect of the present invention provides a high-capacity amorphous carbon-based negative electrode material prepared by the preparation method described above.

[0020] The third aspect of the present invention provides an application of the high-capacity amorphous carbon-based negative electrode material as described above in the preparation of lithium / sodium ion batteries.

[0021] The beneficial effects of the present invention are as follows:

[0022] 1. The present invention introduces a large number of oxygen-containing functional groups into the crushed carbon source precursor through strong oxidation, expands the carbon layer spacing (≈0.4nm), and then obtains disordered block-shaped amorphous carbon negative electrode materials through high-temperature carbonization. During the high-temperature carbonization process, the heteroatoms introduced by the strong oxidant are converted into gases such as CH4 and CO2 and leave the surface of the carbon source, reducing the surface defects of the carbon source. The first coulomb efficiency is high, and the method and process are simple, which can be applied to large-scale industrial production;

[0023] 2. Select a strong oxidant to deeply oxidize the precursor, introduce a large number of oxygen-containing functional groups, and oxidize the inert groups on the edge of the polygonal carbon ring into oxygen-containing active groups, further overcoming the shortcomings of low first coulombic efficiency, low specific capacity and poor rate performance of ordinary amorphous carbon, and showing a specific capacity much higher than that of ordinary amorphous carbon (>380mAh g -1 ), meet the demand of lithium / sodium ion batteries for negative electrode materials. In one embodiment of the present invention, the amorphous carbon-based negative electrode material is applied to sodium ion batteries, and the first coulombic efficiency reaches ~90%; in another embodiment of the present invention, the amorphous carbon-based negative electrode material is applied to lithium ion batteries, and the first coulombic efficiency reaches 79%.

[0024] 3. In some embodiments of the present invention, the carbon source precursor after crushing is pre-carbonized before deep oxidation to enhance the stability of the carbon layer structure and avoid the structure of the carbon source being destroyed by strong oxidants, which may lead to the collapse of the carbon layer and cause carbon loss; pre-carbonization treatment is beneficial to reduce the defects formed on the carbon surface after strong oxidation and further improve the first coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0026] Figure 1 The first three cycles of sodium ion battery charge and discharge curves of the amorphous carbon negative electrode prepared in Example 1 at a current density of 0.05 A / g.

[0027] Figure 2 This is a graph of the sodium ion battery rate performance of the amorphous carbon negative electrode prepared in Example 1.

[0028] Figure 3 These are the SEM and TEM images of the amorphous carbon negative electrode prepared in Example 1.

[0029] Figure 4 The first three cycles of sodium ion battery charge and discharge curves of the amorphous carbon negative electrode prepared in Comparative Example 1 at a current density of 0.05 A / g.

[0030] Figure 5 This is a graph of the sodium ion battery rate performance of the amorphous carbon negative electrode prepared in Comparative Example 1.

[0031] Figure 6 These are the SEM and TEM images of the amorphous carbon negative electrode prepared in Comparative Example 1.

[0032] Figure 7 These are the first three charge and discharge curves of the amorphous carbon negative electrode prepared in Example 10 in a lithium-ion battery.

[0033] Figure 8 Elemental analysis characterization diagram of the amorphous carbon negative electrode prepared in Example 1, Example 2 and Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0035] A high-capacity amorphous carbon-based negative electrode material and a preparation method thereof, wherein the preparation method comprises the following steps: ① crushing the precursor carbon source, sieving to d 50 The value is between 3 and 20 μm; ② subjecting the obtained precursor to a deep oxidation reaction with a strong oxidant; ③ washing the precursor obtained in step ② with deionized water and filtering it to neutrality; ④ subjecting the treated precursor to a high-temperature carbonization treatment under an inert atmosphere, with the temperature set at 1000 to 1700 °C for 1 to 6 hours, and the heating rate set at 1 to 10 °C min -1 , that's it.

[0036] The precursor carbon source is one or more of asphalt, coconut shell charcoal, petroleum coke, coal, palm, bamboo powder, cellulose, wood powder, lignin, corn stalks, starch or phenolic resin; the strong oxidant is a mixture of one or more of iodic acid HIO3, concentrated sulfuric acid H2SO4, perchloric acid HClO4, concentrated hydrochloric acid HCI, concentrated nitric acid HNO3 and manganese dioxide MnO2, and the molar concentration of the strong oxidant is 5-20 mol L -1 ; The oxidation reaction speed is 200-800r / min; the inert gas is Ar or N2.

[0037] In order to make the objectives, technical solutions and advantages of the present invention more clear, some specific embodiments of the present invention will be further described in detail below.

[0038] Example 1

[0039] The precursor coconut shell charcoal is crushed and sieved to d 50 The value is 10μm; 5g of coconut shell carbon precursor was subjected to deep oxidation reaction in a mixed solution of concentrated sulfuric acid H2SO4, concentrated hydrochloric acid HCI and concentrated HNO3 for 60min, with a volume ratio of 1:1:1, the reaction temperature was set to 60℃, and the reaction speed was 500r / min; the obtained sample was washed with deionized water and filtered to neutrality; the above obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1600 °C for 2 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0040] like Figure 1 , the first three cycles of sodium ion battery charge and discharge curves of the amorphous carbon negative electrode prepared in Example 1 at a current density of 0.05 A / g.

[0041] like Figure 2 , sodium ion battery rate performance diagram of the amorphous carbon negative electrode prepared in Example 1.

[0042] like Figure 3 , SEM and TEM images of the amorphous carbon negative electrode prepared in Example 1.

[0043] Example 2

[0044] The precursor coconut shell charcoal is crushed and sieved to d 50 The value is 10μm; 5g of coconut shell carbon precursor was subjected to deep oxidation reaction for 120min in a mixed solution of concentrated sulfuric acid H2SO4, concentrated hydrochloric acid HCI and concentrated HNO3, with a volume ratio of 1:1:1, a reaction temperature of 60℃, and a reaction speed of 500r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1500 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0045] Example 3

[0046] The precursor bamboo powder is crushed and sieved to d 50 The value is 10μm; 5g of bamboo powder precursor was subjected to deep oxidation reaction in concentrated HCI solution for 30min, the reaction temperature was set to 60℃, and the reaction speed was 500r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1500 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0047] Example 4

[0048] The precursor bamboo powder is crushed and sieved to d 50 The value is 10μm; 5g of bamboo powder precursor was subjected to deep oxidation reaction in concentrated HNO3 solution for 30min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1500 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0049] Example 5

[0050] The precursor bamboo powder is crushed and sieved to d 50 The value is 10μm; 5g of bamboo powder precursor was subjected to deep oxidation reaction in concentrated H2SO4 solution for 30min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1500 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0051] Example 6

[0052] The precursor bamboo powder is crushed and sieved to d 50 The value is 10μm; 5g of bamboo powder precursor was subjected to deep oxidation reaction in concentrated HNO3 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1400 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0053] Example 7

[0054] The precursor asphalt is crushed and sieved to d50 The value is 10μm; 5g of asphalt precursor was subjected to deep oxidation reaction in concentrated HNO3 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1400 °C for 3 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0055] Example 8

[0056] The precursor coconut shell charcoal is crushed and sieved to d 50 The value is 10 μm; 5 g of coconut shell carbon precursor was loaded into a tube furnace and heated at 40 ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 600 °C for 2 h with a heating rate of 5 °C min -1 , and then take it out after cooling to room temperature; the obtained sample was subjected to deep oxidation reaction in concentrated HNO3 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the above obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.500 °C for 2 h, with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0057] Example 9

[0058] The precursor coconut shell charcoal is crushed and sieved to d 50 The value is 10 μm; 5 g of coconut shell carbon precursor was loaded into a tube furnace and heated at 40 ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 600 °C for 2 h with a heating rate of 5 °C min -1 , and then take it out after cooling to room temperature; the obtained sample was subjected to deep oxidation reaction in concentrated H2SO4 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the above obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.500 °C for 2 h, with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0059] Example 10

[0060] The precursor asphalt is crushed and sieved to d 50 The value is 10μm; 5g of asphalt precursor was subjected to deep oxidation reaction in concentrated H2SO4 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1000 °C for 4 h with a heating rate of 2 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0061] like Figure 7 , the first three charge and discharge curves of the amorphous carbon negative electrode prepared in Example 10 in a lithium-ion battery.

[0062] Embodiment 11

[0063] The precursor asphalt is crushed and sieved to d 50 The value is 10μm; 5g of asphalt precursor was subjected to deep oxidation reaction in concentrated H2SO4 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.5 % and heat treated at 1000 °C for 3 h with a heating rate of 2 °C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0064] Example 12

[0065] The precursor asphalt is crushed and sieved to d 50 The value is 10μm; 5g of asphalt precursor was subjected to deep oxidation reaction in concentrated H2SO4 solution for 180min, the reaction temperature was set to 60℃, and the reaction speed was 300r / min; the obtained sample was washed with deionized water and filtered to neutrality; the obtained sample was placed in a tube furnace and heated at 40ml min -1 Ar atmosphere was introduced at a flow rate of 1.34°C and heat treated at 900°C for 3 h with a heating rate of 2°C min -1 After cooling to room temperature, the mixture is taken out to obtain a deeply oxidized amorphous carbon negative electrode material.

[0066] Comparative Example 1

[0067] The precursor coconut shell charcoal is crushed and sieved to d 50The value is 10μm; 5g coconut shell carbon precursor was loaded into a tube furnace, and Ar atmosphere was introduced at a flow rate of 40ml / min, and heat treated at 1600℃ for 2h, with a heating rate of 5℃min -1 After cooling to room temperature, the mixture was taken out to obtain an amorphous carbon negative electrode material.

[0068] like Figure 4 , the first three cycles of sodium ion battery charge and discharge curves of the amorphous carbon negative electrode prepared in Comparative Example 1 at a current density of 0.05 A / g.

[0069] like Figure 5 , sodium ion battery rate performance diagram of the amorphous carbon negative electrode prepared in Comparative Example 1.

[0070] like Figure 6 , SEM and TEM images of the amorphous carbon negative electrode prepared in Comparative Example 1.

[0071] According to actual needs, technicians in this field can select any one or more strong oxidants selected from iodic acid HIO3, concentrated sulfuric acid H2SO4, perchloric acid HClO4, concentrated hydrochloric acid HCI, concentrated nitric acid HNO3 and manganese dioxide MnO2 to mix and perform deep oxidation treatment on amorphous carbon. The molar concentration of the strong oxidant is 5-20 mol L -1 The obtained amorphous carbon is heat-treated under an inert gas, cooled to room temperature and taken out to obtain a high-capacity deeply oxidized amorphous carbon-based negative electrode material.

[0072] As shown in Tables 1 and 2, the performance of amorphous carbon negative electrode materials prepared by the present preparation method using different strong oxidants and different amorphous carbons is slightly different, but the performance is significantly improved compared to amorphous carbon materials that have not undergone deep oxidation.

[0073] Table 1. Comparison of sodium ion battery performance of amorphous carbon negative electrode materials with different oxidation depths

[0074]

[0075] Table 2 Comparison of lithium-ion battery performance of amorphous carbon negative electrode materials with different oxidation depths

[0076]

[0077] The first charge capacity and first coulomb efficiency of the sodium ion battery were tested by the half-cell test method for the amorphous carbon negative electrode materials in Examples 1 to 9 and Comparative Example 1, and the results are listed in Table 1. The half-cell test method is as follows: the prepared deep oxidized amorphous carbon, conductive carbon black and sodium alginate are mixed evenly in a mass ratio of 8:1:1, and deionized water is added to prepare a slurry. The slurry is evenly coated on aluminum foil and dried in a vacuum drying oven at 80°C for 12 hours. The surface mass loading of amorphous carbon is about 1.5 to 3 mg cm -2Glass fiber (GF / D) was used as the separator, and the electrolyte was 1M NaPF6, dimethyl ether (DME) solution. The button cell was assembled in an argon glove box (H2O, O2 < 0.1ppm). A LAND CT3002A battery tester (LAND) was used to test the battery at 0.001~2.5V (Vs.Na + As shown in Table 1, the charge and discharge capacity of the amorphous carbon negative electrode material of Example 1 is significantly greater than that of Comparative Example 1, with a capacity increase of 80 mAh g -1 , the first coulombic efficiency increased by ~4%.

[0078] The first charge capacity and first coulomb efficiency of the lithium-ion battery were tested for the amorphous carbon negative electrode materials in Examples 10 to 12 using a half-cell test method, and the results are listed in Table 2. The half-cell test method is as follows: the prepared deep oxidized amorphous carbon, conductive carbon black and polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1, and a slurry is prepared using N-methylpyrrolidone (NMP) as a solvent. The slurry is evenly coated on a copper foil and dried in a vacuum drying oven at 80°C for 12 hours. The surface mass loading of the amorphous carbon is about 1.5 to 3 mg cm -2 . Celgard 2400 was used as the separator, 1M LiPF6 was used as the electrolyte, and propylene carbonate (PC), methyl carbonate (EMC) and dimethyl carbonate (DMC) solutions with a volume ratio of 1:1:1 were used for assembly. The LANDCT3002A battery tester (LAND) was used to test the battery at 0.001~2.5V (Vs.Li + / Li) voltage range, the charge and discharge results of the half-cell were obtained.

[0079] The above disclosure is only a preferred embodiment of the present invention and cannot be used to limit the scope of rights of the present invention. Therefore, any modification, equivalent substitution or improvement made within the spirit and principle of the present invention is still within the scope of the present invention.

Claims

1. A method for preparing a high-capacity amorphous carbon-based negative electrode material, characterized in that: The following steps are involved: ① Crush the precursor carbon source and sieve it to d 50 The value is between 3 and 20 μm; ② subjecting the obtained precursor to an oxidation reaction with a strong oxidant at a reaction temperature of 40 to 120° C. and a reaction time of 30 to 240 min; ③ Wash the precursor obtained in step ② with deionized water and filter until it is neutral; ④ Treat the precursor treated in step ③ with high temperature carbonization for 1 to 6 hours under inert gas, and the temperature of high temperature carbonization is set to 1000 to 1700°C.

2. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The precursor carbon source includes one or more of asphalt, coconut shell charcoal, petroleum coke, coal, palm, bamboo powder, cellulose, wood powder, lignin, corn stalks, starch, and phenolic resin.

3. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The strong oxidant includes one or more of iodic acid HIO3, concentrated sulfuric acid H2SO4, perchloric acid HClO4, concentrated hydrochloric acid HCI, concentrated nitric acid HNO3, and manganese dioxide MnO2.

4. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The molar concentration of the strong oxidant is 5-20 mol L -1 .

5. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The reaction speed of step ② is 200-800 r / min.

6. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The heating rate of step ④ high temperature carbonization is set to 1-10°C min -1 , gas flow rate is 10~40ml min -1 .

7. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The inert gas is Ar or N2.

8. The method for preparing a high-capacity amorphous carbon-based negative electrode material according to claim 1, characterized in that: The precursor obtained by crushing and sieving in step ① is carbonized under inert gas for 1 to 12 hours before step ② is performed, and the carbonization temperature is set to 200 to 800°C.

9. A high-capacity amorphous carbon-based negative electrode material, characterized in that: The preparation method is as described in any one of claims 1 to 8.

10. Use of the high-capacity amorphous carbon-based negative electrode material according to claim 9 in the preparation of lithium / sodium ion batteries.